The Spanish Party System and the Issue of Assigning Responsibility - Sroka, Anna (Political Preferences, 2015)
The article addresses the dependency between the level of institutionalization present in the Spanish party system, electoral accountability and assigning responsibility. The primary research objective of this article is to determine the extent to which electoral volatility is present in Spain, both at the aggregate and individual level, which is a measure of the degree of institutionalization reached by a party system. Next, the dependency between electoral volatility and fluidity of elites at the electoral and parliamentary level is analysed. This allows for an answer to the question of whether there is a problem in Spain with assigning responsibility, having regard to the fact that the presence of extensive electoral volatility among both voters and political elites makes it difficult to speak of effective accountability. Key words: party system, Spanish party system, assigning responsibility, electoral accountability